N-Terminal Pro-B-Type Natriuretic Peptide Levels for Risk Prediction in Patients With Heart Failure and Preserved Ejection Fraction According to Atrial Fibrillation Status. (March 2019) - Kristensen, Søren L.; Mogensen, Ulrik M.; Jhund, Pardeep S.; Rørth, Rasmus; Anand, Inder S.; Carson, Peter E.; Desai, Akshay S.; Pitt, Bertram; Pfeffer, Marc A.; Solomon, Scott D.; Zile, Michael R.; Køber, Lars; et al.
Abstract : Background: NT-proBNP (N-terminal pro-B-type natriuretic peptide) is useful in diagnosis and prognostication in heart failure (HF). We examined the relationship between NT-proBNP and outcomes in patients with HF and preserved ejection fraction, with and without atrial fibrillation (AF). Methods and Results: Among 3835 HF with preserved ejection fraction patients enrolled in the I-Preserve (Irbesartan in Heart Failure With Preserved Systolic Function trial) or TOPCAT trial (Treatment of Preserved Cardiac Function in Heart Failure With an Aldosterone Antagonist), 719 (19%) patients had AF on their baseline ECG. Median (Q1–Q3) levels of NT-proBNP were 1286 pg/mL (778–2072) in those with AF and 288 pg/mL (122–704) in those without ( P <0.001). We analyzed patients using 4 NT-proBNP bands: <400, 400 to 999 (reference), 1000 to 1999, and ≥2000 pg/mL. The event rates for the primary composite outcome of cardiovascular death or HF hospitalization were higher in patients with AF versus patients without or those without without AF in the lowest NT-proBNP band (<400 pg/mL; 8.0 versus 3.2 per 100 patient-years), whereas for the higher bands the opposite was true (1000–1999 pg/mL; 11.4 versus 13.2 per 100 patient-years and ≥2000 pg/mL; 17.4 versus 25.6 per 100 patient-years). In adjusted analyses, higher NT-proBNP levels were less predictive of HF hospitalization than mortality in patients with AF compared with those without. Conclusions: Event rates in HF with preserved ejection fraction patients without AF and with NT-proBNP <400 pg/mL are low. Among patients with NT-proBNP ≥400 pg/mL, the relationship between NT-proBNP and outcomes differs with lower absolute risk in patients who have AF compared with those who do not have AF. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifiers: NCT00094302 and NCT00095238. Abstract : Supplemental Digital Content is available in the text.